1997
DOI: 10.1002/(sici)1520-6823(1997)5:2<50::aid-roi2>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin converting enzyme inhibitor captopril does not prevent acute gastrointestinal radiation damage in the rat

Abstract: Retrospective examination of acute gastrointestinal (GI) lethality in our rat bone marrow transplantation studies showed indication of a protective effect, with a dose modifying factor (DMF) of 1.06 (95% confidence interval: 0.99–1.12). A randomized study, using the same experimental design, was conducted specifically to look for GI protection. Animals were randomized into captopril or non‐drug arms and irradiated in a 6‐fraction total body irradiation regimen, followed by bone marrow transplantation. Rats rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…In both the vehicle- and Captopril-treated groups, circulating lymphocytes remained lower for up to 2 months post-irradiation, whereas platelets returned to normal within 1 month. This is in agreement with Moulder and Fish who showed that Captopril did not prevent acute Gl radiation-induced damage [49]. …”
Section: Resultssupporting
confidence: 92%
“…In both the vehicle- and Captopril-treated groups, circulating lymphocytes remained lower for up to 2 months post-irradiation, whereas platelets returned to normal within 1 month. This is in agreement with Moulder and Fish who showed that Captopril did not prevent acute Gl radiation-induced damage [49]. …”
Section: Resultssupporting
confidence: 92%
“…While there could be some overlap in time between the lung and renal morbidity, they can be distinguished in individual rats based on whether euthanasia was based on pneumonitis or nephropathy criteria. Enalapril had no effect on the early (ARS) phase, which is not unexpected because enalapril did not start until 5 days after PBI, and we have previously shown that ACEi do not mitigate GI (11) or hematological (12) radiation-induced injury in this model. Thereafter, both the enalapril fixed-dose and the enalapril escalated-dose groups showed significant mitigation benefit compared to irradiated rats not receiving drug (Table 1).…”
Section: Resultssupporting
confidence: 50%
“…We do not observe an effect of ACEIs/ARBs on radiation-related toxicities in the current study. However, prior preclinical studies have also not observed an effect of these medications on the gastrointestinal side effects of radiation, 36 which are likely to predominate in our patient population.…”
Section: Discussionmentioning
confidence: 76%